Characterization of spark plasma sintered TiC ceramics reinforced with graphene nano-platelets. Issue 11 (1st August 2020) - Nguyen, Thang Phan; Pazhouhanfar, Yaghoub; Delbari, Seyed Ali; Le, Quyet Van; Shaddel, Shahrzad; Pazhouhanfar, Morteza; Sabahi Namini, Abbas; Shokouhimehr, Mohammadreza; Shahedi Asl, Mehdi
Abstract: This research aims to scrutinize the impact of graphene additive on the consolidation behavior, microstructure and physical-mechanical qualifications of TiC-based materials. For this purpose, two specimens, namely monolithic TiC and TiC-5 wt% graphene, were produced using the spark plasma sintering (SPS) method at 1900 °C. An external pressure of 40 MPa was applied during the sintering, and the ceramics were held at the maximum temperature for 10 min. The characteristics of SPSed samples were studied using scanning electron microscopy (SEM) and X-ray diffraction (XRD). Although adding graphene had no notable effect on the sinterability of TiC, it led to an increment in the flexural strength of graphene-doped sample. The microstructural assessment revealed the positive influence of graphene additive on obtaining a finer microstructure. The phase analysis confirmed the appearance of a non-stoichiometric hexagonal TiCx and different allotropes of carbon in the samples. Finally, the highest values for Vickers hardness ( 3130 HV0.1Kg ) and flexural strength ( 530 MPa) were attained for the monolithic TiC and graphene-reinforced samples, respectively.